(untitled) (European Journal of Child Development, Education and Psychopathology, 2015)
European Convergence process has focused the debate in recent years within the university and social environment with the arrival of European Higher Education Area (EHEA). In this context there are important issues such as, among others, the unification of European systems and the recognition of qualifications at international level, changes in the teaching model, using new methods and forms of assessment, at present. The instrument used was a questionnaire created "ad hoc" which explores the issues raised, which was applied to 116 students of the degree concerned. The results showed that students on the one hand, positively do not appreciate the reforms introduced by the EHEA even claim to have a low awareness on issues related to mobility and international recognition of their qualifications. At the methodological level, it is worth learning the inclusion of skills and the use of active methodologies that enable a comprehensive education of students.